NGHIÊN CỨU ẢNH HƯỞNG CỦA KÍCH THƯỚC HẠT ĐẾN KHẢ NĂNG HẤP PHỤ THAN HOẠT TÍNH DẠNG BỘT - Sáng, Trần Quang; Khuê, Đỗ Ngọc; Du, Lê Huy (Vietnam Journal of Chemistry, 2012)
Activated carbon powder has been known recently for its applications, such as toxic contaminated water treatment, toxic digestive organs filter, blood dialysis for drug addicts, electromagnetic waves adsorption materials, etc. This paper presents research results of the changes of activated carbon particle size that affect adsorption capacity and capillary structure of Tra Bac activated carbon.